(untitled) (Actual Problems of Psychology in Educational Institutions, 2021)
The article is devoted to the study of reflection in teenage years. We have reviewed and analyzed scientific sources on this topic. The views of scientists on this phenomenon and its significance in teenage years were considered. Also, diagnostics of the level of development of reflection in modern teenagers was implemented using the method of determining the level of reflexivity by A. V. Karpova, V. V. Ponomareva. Further analysis of the diagnostic results allowed us to draw conclusions regarding the existing level of self-reflection in teenage years. Also, psychological and pedagogical recommendations were developed to increase the level of self-reflection in modern teenagers.